PROFIL INTELIGENSI REMAJA PUTRI YANG TINGGAL DI PANTI ASUHAN - Vera Imanti; Triyono Triyono (Academic Journal of Psychology and Counseling, 2021)
Adolescent who are currently sitting on high schools or should be equal begin to prepare for a career on the next one. Career determination is based on desire and potential of interests and talents. To understand these interests and potential, a measurement must be taken, one of them with an intelligence measuring instrument. The purpose of this study is to provide a profile of the adolescent girls intelligence living at the female orphanage in Solo city. This study is a descriptive quantitative study. The measuring instrument uses the IST intelligence test instrument. The career interest survey uses the RMIB. The subjects used were 8 beneficiaries in the female orphanage. Determination of the subject using purposive sampling, namely adolescent girls who sit at the high school level or equivalent. The measurement results show 2 people with IQ in the category above average, and 6 people with the average category. Of the 5 categorizations, no subject was in the low category. While the categories indicated by 3 aspects, namely, verbal ability, analytical power, and memory